CULTIVATING MARINE LEADERSHIP CHARACTER THROUGH MULTICULTURAL BOARDING-SCHOOL SYSTEM - Aan Fardani Ubaidillah; Ibrahim Bafadal; Nurul Ulfatin; Achmad Supriyanto (LPMPP Universitas Negeri Yogyakarta, 2020)
The internalization of character values in the boarding-schools should ideally be designed to answering the challenges of the context of Indonesia as a multicultural country. This study aims to reconstruct the character cultivation through the multicultural boarding school system as an internalization model of marine leadership characters. This study employed a single-holistic case study in a Senior High School of Taruna Nala, East Java, Indonesia, that implemented a boarding school system. The data collection was conducted through in-depth interviews, participant observation, and documentary analysis, and the results was presented interactively. The data sources studied were determined by purposive sampling and snowball sampling. The data validity was tested with four criteria: credibility, dependability, confirmability, and transferability. This study found that the character of maritime leadership is the reponsive (tanggap), tough (tanggon), and agile (trengginas) as unique-intelligent characters that must be mastered by senior high schools in Indonesia as a maritime country. To make it happens, the internalization of character values can be done through a cultivation model, like in planting, consisting of: (1) determining the goals, (2) the seeds selection, (3) land cultivation, (4) planting the seeds, (5) maintenance, and (6) fertilization. The model is carried out in full through the boarding system education system.